THE DEVELOPMENT OF IMAGE PROCESSING METHOD ON THE AUTOMATIC READING SYSTEM OF THE GLASS THERMOMETER USING A DIGITAL CAMERA - Gianto Gianto; Vera Firmansyah; Irwan Setiawan; Achsan Rifani (Program Studi Fisika Universitas Negeri Jakarta, 2021)
The reading performance of an analog thermometer, Liquid in Glass Thermometer (LiGT), can be improved using a digital camera. The aim is to minimize the human error on the reading of LiGT and increase the accuracy of temperature measurement results. In order to achieve an accurate result, a robust image processing method is required in the measurement. In this work, the LiGT image generated using a digital camera is analyzed using the technique in HSV color space which consists of some image processing methods (e.g., thresholding, morphology filter). The type of LiGT used is the glass thermometer with the colored liquid. There are three main parts to this developed technique process, i.e., identifying the scale of LiGT to calculate the pixel per temperature unit value (ppt), segmentation of the liquid column, and calculate the temperature based on the ppt value. Through simulation with a synthetic image, we demonstrate that the developed technique in this work has successfully read (measured) the temperature value of the LiGT (having a scale unit of 1oC) with a measurement error of 0.04oC. In the experimental results, we also report the developed technique performed on a real image of LiGT.